Student engagement and the academic library - Snavely, Loanne (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2012)
"This unique book explores exciting programs and initiatives that can both engage undergraduate students with academic libraries and assist academic librarians in creating a vibrant library atmosphere"-- Provided by publisher.